Description of a very dense meteorite collection area in western Atacama: Insight into the long‐term composition of the meteorite flux to Earth. (17th February 2016) - Hutzler, Aurore; Gattacceca, Jérôme; Rochette, Pierre; Braucher, Régis; Carro, Bertrand; Christensen, Eric J.; Cournede, Cécile; Gounelle, Matthieu; Laridhi Ouazaa, Nejia; Martinez, Rodrigo; Valenzuela, Millarca; Warner, Michael; et al.
Abstract: We describe the geological, morphological, and climatic settings of two new meteorite collections from Atacama (Chile). The "El Médano collection" was recovered by systematic on‐foot search in El Médano and Caleta el Cobre dense collection areas and is composed of 213 meteorites before pairing, 142 after pairing. The "private collection" has been recovered by car by three private hunters and consists of 213 meteorites. Similar to other hot desert finds, and contrary to the falls and Antarctica finds, both collections show an overabundance of H chondrites. A recovery density can be calculated only for the El Médano collection and gives 251 and 168 meteorites larger than 10 g km −2, before and after pairing, respectively. It is by far the densest collection area described in hot deserts. The Atacama Desert is known to have been hyperarid for a long period of time and, based on cosmic‐ray exposure ages on the order of 1–10 Ma, to have been stable over a period of time of several million years. Such a high meteorite concentration might be explained invoking either a yet unclear concentration mechanism (possibly related to downslope creeping) or a previously underestimated meteorite flux in previous studies or an average terrestrial age over 2 Myr. This last hypothesis is supported by the high weathering grade of meteorites and by the common terrestrial fragmentation (with fragments scattered over a few meters) of recovered meteorites.